2010
DOI: 10.1189/jlb.0809585
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic PI3K isoforms p110γ and p110δ contribute to B cell development and maintenance, transformation, and proliferation

Abstract: Class I PI3K-dependent signaling regulates cell proliferation, differentiation, and survival. Analysis of gene-deficient mice revealed specific roles for the hematopoietically expressed PI3K catalytic subunits, p110gamma and p110delta, in development and function of T and B lymphocytes. However, the functional redundancy between these two PI3K isoforms in the B cell lineage remains unclear. Here, we demonstrate that p110delta and p110gamma are expressed in B cells at early developmental stages. Normal B cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 50 publications
1
52
1
Order By: Relevance
“…These accumulating data indicate that PI3Kd appears to be the main isoform involved in the regulation of B cell functions, including their maturation and activation. However, Beer-Hammer et al revealed that the absence of p110g and p110d impaired B cell maturation to a significantly higher extent than the loss of p110d alone (Beer-Hammer et al, 2010). Likewise, p110g/p110d double-deficient splenocytes presented a proliferation defect following LPS stimulation, resulting in a decrease in survival.…”
Section: Pi3k In B Cell Functionmentioning
confidence: 99%
“…These accumulating data indicate that PI3Kd appears to be the main isoform involved in the regulation of B cell functions, including their maturation and activation. However, Beer-Hammer et al revealed that the absence of p110g and p110d impaired B cell maturation to a significantly higher extent than the loss of p110d alone (Beer-Hammer et al, 2010). Likewise, p110g/p110d double-deficient splenocytes presented a proliferation defect following LPS stimulation, resulting in a decrease in survival.…”
Section: Pi3k In B Cell Functionmentioning
confidence: 99%
“…In T cells, p110γ plays a role in early development and is important for trafficking of activated effector cells (14, 15). One study reported that mice lacking both p110δ and p110γ had greater defects in B cell survival and proliferation compared to p110δ knockout alone (16). The effects of chemical p110γ inhibition on B cell function have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The p110g subunit has been suggested to play a prominent role in immunity and inflammation, in particular by regulating migration of multiple cell types such as neutrophils and macrophages to the site of inflammation (Hirsch et al, 2000;Li et al, 2000). Furthermore, it has been found to have a minor role in lymphocyte development (Beer-Hammer et al, 2010;Sasaki et al, 2000), as well as T cell proliferation (Ladygina et al, 2013). Moreover, p110g is implicated in multiple human diseases such as atherosclerosis (Zotes et al, 2013) and is thus seen as a promising therapeutic target in many inflammatory disorders (Costa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%